2007
DOI: 10.33997/j.afs.2007.20.1.009
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Study of Effect of Short and Long-term Copper Sulfate Bath on Gill in Grass Carp, Ctenopharyngodon idella

Abstract: Grass carp were exposed to two therapeutic concentrations of copper sulfate (10 mgxL-1 in 1 hour and 1 mgxL-1 in 24 hours). Twenty-four hours after the copper sulfate baths, the histopathology of the gills was studied. The observed lesions in gills after short and long term baths were: mucus coagulation and accumulation of cellular debris on the epithelium of lamellae and inter lamellar regions, lamellar edema, hemorrhage, hyperplasia, epithelial cell necrosis, congestion and aneurysm (telangiectasis) in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…the highest levels of T4 and T3 showed in the highest salinity 30 psu followed by the salinities (15, 7.5 and 1.5) psu respectively in all times, and this in agreement with many studies showed an increase in thyroid hormones with salinity increase like the study of McCormick and Saunders (1990) showed that in juvenile Atlantic salmon (Salmo salar) following acute exposure to seawater (30 ppt), plasma T4 increased 80 % in the first 6 hrs., declined to initial levels after 24 hrs., and remained stable for 18 days, there-after. Peyghan et al (2013) results showed that increasing water salinity can have significant effect on thyroid activity by decreasing T3 and increasing T4 level in serum of grass carp in experimental condition. Results of Movahedinia et al (2010) on A. latus held in different salinities indicated that thyroid hormone levels in plasma (T3) showed a small rise that quickly return to normal after 12 hrs.…”
Section: Discussionmentioning
confidence: 85%
“…the highest levels of T4 and T3 showed in the highest salinity 30 psu followed by the salinities (15, 7.5 and 1.5) psu respectively in all times, and this in agreement with many studies showed an increase in thyroid hormones with salinity increase like the study of McCormick and Saunders (1990) showed that in juvenile Atlantic salmon (Salmo salar) following acute exposure to seawater (30 ppt), plasma T4 increased 80 % in the first 6 hrs., declined to initial levels after 24 hrs., and remained stable for 18 days, there-after. Peyghan et al (2013) results showed that increasing water salinity can have significant effect on thyroid activity by decreasing T3 and increasing T4 level in serum of grass carp in experimental condition. Results of Movahedinia et al (2010) on A. latus held in different salinities indicated that thyroid hormone levels in plasma (T3) showed a small rise that quickly return to normal after 12 hrs.…”
Section: Discussionmentioning
confidence: 85%
“…More recent experiments confirm the involvement of TH in salinity acclimation. Freshwater climbing perch ( Anabas testudineus ) and grass carps placed at a high salinity underwent a transient increase in plasma T4 levels [ 49 , 50 ]. In addition, gilthead seabreams living in high salinity habitats and switching to low salinity habitats had higher dio2 expression levels and higher free T4 and T3 levels than controls but, strikingly, did not show changes in TSH β levels.…”
Section: Salinity Acclimationmentioning
confidence: 99%
“…It is essential to recognise that the optimal salinity level varies for each sh species, affecting their growth and survival differently (Peyghan et al 2013; Elarabany et al 2017). The initial impact of salinity on sh is evident through osmotic adjustments.…”
Section: Introductionmentioning
confidence: 99%